Promulgation in the Legislative Practice of Pope Francis - Gałkowski, Tomasz (Prawo Kanoniczne, 2023)
Pope Francis has made several significant changes to the Code of Canon Law. They aroused the interest of experts in canon law, not only because of substantive changes, but above all because of the ways of promulgation of the new rules. By presenting the problems related to the promulgation and the consequences of Francis' practice for the community and the rights of the faithful, the author of the study believes that they are also an interesting challenge for legal knowledge, directing from scientia to ars iuris.